In vivo evaluation of a nanoantibiotic-integrated collagen-chitosan scaffold for bone regeneration in a critical-size rat defect model - Mohd Zayi, Nora Azirah; Mohamed Halim, Muhammad Lutfi; Harun @ Ismail, Ahmad Fahmi; Arzmi, Mohd Hafiz; Mohamad, Mohd Yusof; Subramaniam, Pram Kumar (IIUM Press, International Islamic University Malaysia, 2024)
Background: Bone loss resulting from periodontal disease, trauma, or anatomical factors is a prevalent challenge in periodontology. This study evaluates the effectiveness of a biodegradable collagen-chitosan scaffold loaded with metronidazole nanoantibiotics to enhance bone regeneration in vivo using a Sprague-Dawley rat skull defect model. The scaffold was surgically placed in critical-size defects, with groups either receiving scaffolds loaded with metronidazole nanoparticles (MNP), empty scaffolds, or no scaffold. The aim of the research is to offer an alternative to conventional non-biodegradable scaffolds, which often require additional surgical removal.